EFFECT OF TEMPERATURE ON THE LIPID CONTENT IN Nannochloropsis oculata, Dunaliella salina AND Isochyrsis galbana FOR BIODIESEL PRODUCTION - V. RAMESH KUMAR,; G. MELCHIAS, (International Journal of Pharma and Bio Sciences, 2014)
Microalgae, an autotrophic organism has been established as a potential source for biodiesel production. Suitable candidates from marine origin have been selected as viz., Nannochloropsis oculata, Dunaliella salina, and Isochrysis galbana. The microalgae were grown in controlled conditions and an assessment of their growth rate and lipid productivity were made. To analyze the effect of temperature on the growth of different microalga, temperature stress was induced. Biochemical changes in the culture and changes in fatty acid profiles of the culture before and after temperature stress are reported. Temperature stress increased lipid productivity in microalgae. The lipid obtained from microalgae were converted to biodiesel by chemical transesterification. Also the biodiesel thus obtained was mixed with commercial diesel to produce biodiesel blend in different ratios. The biodiesel properties of Biodiesel 20, Biodiesel 50 and Biodiesel 100 (pure biodiesel), were comparable to that of commercial diesel.